2014
DOI: 10.1021/cm500061f
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Polymerization in a Confined Space: Conjugated Chain/Zeolite Nanocomposites

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…IR/Raman spectroscopy and X‐ray diffraction showed that the host‐guest compound, after ambient pressure recovery, contained polyethylene chains and had a greater bulk modulus than silicalite due to the filling of the pores (Figure a). Using the same zeolite as confining matrix, the same group performed the pressure‐driven‐only polymerization of acetylene: compression up to ∼4 GPa (without light irradiation) induced the penetration of the molecules in silicalite and their polymerization to polyacetylene chains running along the zeolite channels (Figure b) …”
Section: Organized Materials By High‐pressure Confinementmentioning
confidence: 99%
See 1 more Smart Citation
“…IR/Raman spectroscopy and X‐ray diffraction showed that the host‐guest compound, after ambient pressure recovery, contained polyethylene chains and had a greater bulk modulus than silicalite due to the filling of the pores (Figure a). Using the same zeolite as confining matrix, the same group performed the pressure‐driven‐only polymerization of acetylene: compression up to ∼4 GPa (without light irradiation) induced the penetration of the molecules in silicalite and their polymerization to polyacetylene chains running along the zeolite channels (Figure b) …”
Section: Organized Materials By High‐pressure Confinementmentioning
confidence: 99%
“…In this case, the self‐assembly process is controlled by both the confining matrix and the imposed pressure. Recently observed phenomena such as pressure‐induced polymerization or formation of complex supramolecular patterns candidate hyperconfinement as an intriguing route to new materials.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the application of external pressure produces the shortening of the intermolecular distances of confined organic molecules (e.g. ethylene, acetylene) hosted in zeolite channels, inducing polymerization reactions without catalysts or radical initiators [15,16] and contributing to stiffen the structure [17e19].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the possibility of HP-induced polymerization has recently been demonstrated for acetylene and ethylene inserted into the MFI framework. 24,25 Pressure is the most efficient means to reduce intermolecular distances, thereby allowing chemical reactions to occur. 25 The studies performed with 'non-penetrating' media highlighted the crucial influence of the framework type and composition, and the extra-framework content, on zeolite's response to pressure in terms of deformation mechanism and compressibility.…”
Section: Introductionmentioning
confidence: 99%